2014
DOI: 10.1097/qai.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Open-Label Study of 3- Versus 5-Drug Combination Antiretroviral Therapy in Newly HIV-1–Infected Individuals

Abstract: Background To understand whether combination antiretroviral therapy (cART) has been optimized, we asked whether 3-drug protease inhibitor (PI)-based cART intensified with raltegravir and maraviroc and initiated during early infection would improve outcomes when compared to similarly applied 3-drug PI-based cART. Methods 40 newly HIV-1 infected patients were randomized 1:2 to receive 3-drug (N=14) or 5-drug (N=26) therapy. The primary endpoint was the percent of subjects with undetectable plasma viremia using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 29 publications
4
54
1
Order By: Relevance
“…The addition of RAL and MVC alone to suppressive cART did not result in decreases or increases of either cell-associated HIV DNA or ultrasensitive HIV RNA, consistent with prior intensification studies using RAL or MVC[10,12,30]. We did not investigate the level of preintegration episomal DNA (2-LTR circles), but some studies did find transient accumulation of 2-LTR circles with RAL or MVC.…”
supporting
confidence: 86%
“…The addition of RAL and MVC alone to suppressive cART did not result in decreases or increases of either cell-associated HIV DNA or ultrasensitive HIV RNA, consistent with prior intensification studies using RAL or MVC[10,12,30]. We did not investigate the level of preintegration episomal DNA (2-LTR circles), but some studies did find transient accumulation of 2-LTR circles with RAL or MVC.…”
supporting
confidence: 86%
“…This has been previously described and was not found to be associated with any differences in the measurable HIV reservoir after 24 weeks of therapy [9]. Similarly, addition of raltegravir and maraviroc to protease inhibitor-based regimens has been shown to result in rapid reduction of plasma viremia without long-term effect on HIV reservoirs when ART is initiated during primary HIV infection [24,25]. In prior studies, adherence to the intensified five-drug regimens tended to be worse and virologic failure was more common [24,25].…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, addition of raltegravir and maraviroc to protease inhibitor-based regimens has been shown to result in rapid reduction of plasma viremia without long-term effect on HIV reservoirs when ART is initiated during primary HIV infection [24,25]. In prior studies, adherence to the intensified five-drug regimens tended to be worse and virologic failure was more common [24,25]. Interestingly, three of the four participants with virologic failure at week 24 in this study were prescribed the intensified five-drug regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increasing the combination of drugs administered may not be sufficient to eradicate viral reservoirs. Recently, a randomized open-label study of three-versus fivedrug PI-based combination HAART in newly HIV-1-infected individuals also found no significant long-term impact on virologic or immunologic responses at 48 weeks beyond those achieved with standard three-drug PI-based HAART (40). Unlike this recent clinical study, which was limited to monitoring the viral load after 12 weeks of treatment, our studies demonstrated an immediate impact on viral decay kinetics during the first 10 weeks of treatment, which arguably could be of benefit to the infected individuals in preserving their functional immunity.…”
Section: Discussionmentioning
confidence: 99%